The weight of the influence of governments on quality press information - Méndez Nieto, Antonio; León Gross, Teodoro; Paniagua Ronao, Francisco Javier (Estudios sobre el Mensaje Periodístico, 2018)
One-fourth of the information provided by the press –more precisely by the closest general information sections- has its original source in facts which can be linked in a directly or indirect way to a particular government. This is the result of such an investigation on the weight of the information from Central, Regional and Local governments in the press of reference. According to a quantitative methodology, the content analysis offers an evaluation of 29,342 information units in the national newspapers El País and El Mundo, and local newspapers Sur and Málaga Hoy, along 2010. The national press is less permeable to the publication of these contents, compared to the local newspapers. Taking influences as a value of reference, 42% of the news must do with central government, 30% has to do with regional governments and 28% comes from local and provincial corporations.